(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The article provides the results of a comparative analysis of changes in the functional state of the cardiorespiratory system of students of 18-19 years of higher education under the influence of remote sectional classes from different types of fitness (rhythmic and aesthetic gymnastics). To realize the purpose of the study, the peculiarities of the functional state of the cardiovascular system and the system of external respiration of students of the two groups at the beginning and at the end of the academic year were studied using traditional methods and computer program of express evaluation of the functional state of "SHVSM". Results allowed to state in general the positive impact of remote section classes from both types of fitness (rhythmic and aesthetic gymnastics) on the main indicators of the current state Type of response of the circulatory system to physical activity, normalization of cardiac index values, coefficient of efficiency of blood circulation, general peripheral resistance of blood vessels, increasing the potential of the system of external respiration and stability of the body to hypoxia. At the same time, it should be noted that the use of rhythmic gymnastics in the remote sectional exercise has contributed to the reliably more significant, compared to the program of similar lessons with the inclusion of aesthetic gymnastics, positive changes in most parameters of the cardiorespiratory system of the body. It was proved that the completion of the study for the representatives of the rhythmic gymnastics group was characterized by significantly better amounts of heart rate, pulse blood pressure, systolic volume of blood, cardiac index, life capacity of the lungs, respiratory retention time and Skibinsky index. Moreover, among the students of this group, there were higher girls who were engaged in aesthetic gymnastics during the school year, positive rates of improving heart rate (8 times), pulse blood pressure, cardiac index, Robinson index, cost -effectiveness. 1.5 times), vital capacity of the lungs (2 times), time of breathing inhalation (3 times), Skibinsky index (8 times) and hypoxia index 14 times. Thus, the results of the study indicate higher efficiency of use of rhythmic gymnastics in the program of remote sectional classes for students of higher education.